2018 Joint Propulsion Conference 2018
DOI: 10.2514/6.2018-4567
|View full text |Cite|
|
Sign up to set email alerts
|

Determining the Pressure Gain of Pressure Gain Combustion

Abstract: Over the past few decades, there has been significant research into propulsion concepts attempting to employ pressure gain combustion. Pressure gain combustion concepts to date have resulted in dynamic, non-uniform gas flows which are difficult to characterize and compare with more conventional forms of propulsion. This paper proposes a technique to derive for the pressure gain combustion device an equivalent, steady, uniform gas pressure that is available to do work or provide thrust, thereby providing a dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…All of them are suitable for steady-state 0D gas turbine performance simulation. Therein, it is already assumed that the total kinetic energy at combustor exit during exhaust phase is not thoroughly available for work transfer in the turbine (Kaemming & Paxson, 2018). However, the models' performances deviate from each other.…”
Section: Introductionmentioning
confidence: 99%
“…All of them are suitable for steady-state 0D gas turbine performance simulation. Therein, it is already assumed that the total kinetic energy at combustor exit during exhaust phase is not thoroughly available for work transfer in the turbine (Kaemming & Paxson, 2018). However, the models' performances deviate from each other.…”
Section: Introductionmentioning
confidence: 99%
“…However, these data must be condensed to a single representative value for steady-state simulation. Several authors provided guidelines as to which averaging technique is correct for the application [7,14]. The disadvantage of this approach lies in the obtained information, which is ultimately summarized in a representative scalar value.…”
Section: Introductionmentioning
confidence: 99%
“…All have already been used in steady-state zero-dimensional gas turbine performance simulations. Therein, it was already assumed that only a part of the total kinetic energy during the exhaust phase is available for work transfer in the turbine [14]. Nevertheless, the models' performances deviate from each other [19].…”
Section: Introductionmentioning
confidence: 99%
“…1 At the same time, theoretical and experimental studies of detonative combustion concepts came to the conclusion that pressure gain up to 30% might be possible for pulsed detonation combustion 2,3 and rotating detonation combustion. [4][5][6] This great potential has motivated numerous thermodynamic cycle performance studies. Initially, most focused on the generation of thrust from pulse detonation combustors.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies on resonant pulsed combustors have demonstrated a pressure gain of approximately 3% 1 . At the same time, theoretical and experimental studies of detonative combustion concepts came to the conclusion that pressure gain up to 30% might be possible for pulsed detonation combustion 2,3 and rotating detonation combustion 4‐6 …”
Section: Introductionmentioning
confidence: 99%